Against a Nomic Virtue Epistemology - Gómez-Alonso, Modesto (Análisis. Revista de investigación filosófica, 2017)
Abstract In Judgment and Agency, Ernest Sosa argues for a particular methodology –what he calls ‘metaphysical analysis’– whose aim is to provide a speci c sort of explanation of knowledge –a metaphysical explanation–. As I read it, this revolutionary step points to the bulk of the ontological dispositional web that necessarily sustains a virtue epistemology, contributes to a proper understanding of accidentality in epistemology, and breaks the hold of Humean contingency. I will argue that Sosa’s account of the constitution of knowledge is not only able to rule out apparent counterexamples to a robust virtue epistemology, as well as to combine rational integration and knowledge explanation, but that also breaks the Pyrrhonian (and internalist) impasse. I will also argue that a principled distinction between cases of knowledge and cases of mimicking is unavailable to anti-luck virtue epistemologists, so that they face a dilemma between their theory collapsing into a robust virtue epistemology or its collapsing into a form of nomic virtue epistemology. What binds anti-luck virtue epistemologies and nomic theories together is a common problem in binding, one that is absent from a theory, such as Sosa’s theory, that locates knowledge in the domain of higher-order competences and rational guidance. Keywords: Anti-luck virtue epistemology; dispositional directedness; Humean contingency; mimics; nomic necessities. Resumen: En Judgment and Agency, Ernest Sosa defiende una metodología específica –a la que denomina ‘análisis metafísico’– cuya función es la de proporcionar una explicación particular del conocimiento –una explicación metafísica–. Se trata de un procedi- miento signi cativo, que apunta a la red disposicional que necesariamente sostiene a la epistemología de virtudes, contribuye a la comprensión adecuada de la acciden- talidad en epistemología, y rompe el dominio de la contingencia humeana. En este artículo argumento que la explicación que Sosa proporciona de la constitución del conocimiento, además de evitar aparentes contraejemplos para una epistemología de virtudes robusta y de combinar la explicación del conocimiento y la integración racional, es una herramienta fundamental para contrarrestar las intuiciones pirrónicas (e internistas). También argumento que la ‘epistemología de virtudes anti-suerte’ es incapaz de establecer una diferencia razonada entre casos de conocimiento y casos de acierto accidental debidos a la intervención de bloqueadores epistémicos (mimics), de forma que dicha teoría solo puede optar entre una epistemología de virtudes robusta y una epistemología de virtudes nómica. Es el problema de la combinación adecuada de los factores que contribuyen al conocimiento aquello que vincula epistemología de virtudes nómica y epistemología de virtudes anti-suerte. Dicho problema no existe en teorías como la de Sosa, teorías para las que el conocimiento es explicable en función de competencias de segundo orden y guía racional apropiada. Palabras Clave: Bloqueadores epistémicos; contingencia humeana; direccionalidad disposicional; epistemología de virtudes anti-suerte; necesidades nómicas.